Sensitivity Test of Clove Leaf Essential Oil (Syzygium aromaticum) Against Heterotrophic Bacteria Isolated from Food Products - Muhammad Iqbal Filayani; Farida Nur Jana; Fitriyah (JOSAR (Journal of Students Academic Research), 2025)
This study aimed to evaluate the antibacterial activity of clove leaf essential oil (Syzygium aromaticum) against heterotrophic bacteria isolated from food products. Clove leaves were collected from Malang Regency, Indonesia, and the essential oil was extracted via steam-water distillation. Bacterial isolates were obtained from food samples using serial dilution and pour plate techniques. Antibacterial activity was assessed using the agar diffusion method at three oil concentrations (50%, 75%, and 100%), with Amoxicillin trihydrate as the positive control and sterile distilled water as the negative control. The morphological characteristics of the isolates were documented, and inhibition zones were measured. Results indicated that inhibition strength increased with oil concentration up to 75%, with the largest numerical inhibition observed against isolate K2 at 100% concentration (31.3 mm), approaching the positive control’s efficacy. Statistical analyses confirmed that differences among treatments were significant (p < 0.001), except between 75% and 100% concentrations, suggesting a plateau in activity beyond the minimum inhibitory concentration. The findings highlight clove leaf essential oil’s potential as a natural antibacterial agent for food preservation, offering an environmentally sustainable alternative to synthetic antimicrobials. However, in vitro conditions may not fully represent performance in real food matrices, warranting further research on its application, stability, sensory effects, and synergistic combinations with other natural antimicrobials.